2021
DOI: 10.1142/s0218625x21400059
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Two-Dimensional Materials

Abstract: The application areas of two-dimensional (2D) materials, their heterostructures and composites are rapidly expanding — thanks to their extraordinary mechanical, optical, electronic and thermal properties. The family of 2D materials, which are finding a use in applications, is rapidly growing, and now includes graphene, graphene oxide, hexagonal boron nitride and transition-metal dichalcogenide, as well as the recently obtained chemical derivatives, physically modified hybrids and allotropes. New applications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 242 publications
0
6
0
Order By: Relevance
“…1 shows the schematic structures of typical 2D materials which are used to make composites with different materials.
Figure 1 Schematic of typical 2D materials applied in energy storage devices [ 10 ].
…”
Section: Supercapacitors; Emerging Field Of Electro Chemical Energy S...mentioning
confidence: 99%
“…1 shows the schematic structures of typical 2D materials which are used to make composites with different materials.
Figure 1 Schematic of typical 2D materials applied in energy storage devices [ 10 ].
…”
Section: Supercapacitors; Emerging Field Of Electro Chemical Energy S...mentioning
confidence: 99%
“…Two-dimensional materials are those in which electrons can move freely in only two dimensions, including graphene, black phosphorus, and transition metal dichalcogenides [ 14 ]. Two-dimensional materials have exhibited unique optical and electrical properties, including high carrier mobility, tunable band structure, and strong light-matter interaction, which make them widely used in the preparation of optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] Graphene's positive role in composite materials is related to its high electrical conductivity (10 8 S m −1 for pure graphene) [ 21 ] and thermal conductivity, [ 22 ] large surface area (2630 m 2 g −1 ), [ 23,24 ] chemical neutrality, [ 25 ] and environmental friendliness, [ 26 ] which all originate from its unique electronic structure. [ 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…[20] Graphene's positive role in composite materials is related to its high electrical conductivity (10 8 S m À1 for pure graphene) [21] and thermal conductivity, [22] large surface area (2630 m 2 g À1 ), [23,24] chemical neutrality, [25] and environmental friendliness, [26] which all originate from its unique electronic structure. [27] Despite the excellent role of graphene in composite EDLC electrodes, one of the challenges that still remains unsolved is the influence of the compositing method of graphene with AC on the electrochemical properties. As an example, Chen et al [11] reported the fabrication of AC/graphene composite by mixing and annealing a mixture of graphene oxide, KOH, and AC at 800 °C in a furnace under an inert atmosphere.…”
mentioning
confidence: 99%